THE STUDY OF NONIONIC SURFACTANT MICELLES BY SMALL-ANGLE NEUTRON-SCATTERING - Penfold, J; Staples, E; Cummins, P (1992)
Small angle neutron scattering (SANS) has been used to study the structure of nonionic surfactants in a variety of different circumstances. The nature of the adsorption of the alkyl polyoxyethylene oxide nonionic surfactants CnEm on ludox silica sols is described. The evolution of miceller geometry of the nonionic micelles of C16E6 and mixed cationic nonionic micelles is discussed, and the nature of nonionic micelles in less polar solvents is described. © 1992.